(3fgGjI GdEOQGc aj CSQGQ Ydhe GdCadGcs - (3GdJjej GdaGQSqj, CHh YHO Gddg, HOQ GdOjf, eMeO Hf CHj HcQ Hf eMeO, J (B677 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj HgQ GdYbhnd MbGFob ZQGFH UfYJg hTQafj HNOeI CHj GdfUQ jhSa Hf YeQ Hf Ndjd CejQ GdeDefjf hcfJ bO JTQaJ HNOeI NRGFf cJHg GdeYhdI aj EfTGA GdQSGFd aYj GdQSGdI GdXdjI GdeSei HQSGdI GdXd GdeHShW s
(3BNQgG (B:s
(3aUd aj hbJ NQhL GdeSLhf hWQjbI Cf JfXQ Edi QH GdWGdY ef GdbeQ aEf cGf aj GdQHY GdRGFd aGce HSQYI NQhLg hGfXQ CjgeG CSQY GJUGdG HPdc GdchcH Jes
(3CdagG ddedc GdeXaQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\55s
(3cTa GdXfhf (B2\1085s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3Gdadc hGdJfLje hGdejbGJs